Evaluation of Sperm Velocity Parameters with Glutathione and Honey in Skim Milk Based Extenders by CASA on Boer Buck - Araker, Suresh; Tandle, MK; Vinay, PT; Bijurkar, RG; Suranagi, MD; Rao, Jagannath; Kulkarni , S (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The study aimed to evaluate the Boer buck sperm velocity (µm/sec) parameters (VCL: Curvilinear Velocity, VAP: Average Path Velocityand VSL: Straight line Velocity) with 5 mM Glutathione (G) and 1% or 2% Honey (H) in Skim milk (SM) based extenders preserved atrefrigeration temperature for 0, 24, 48 and 72 hrs. A total of 72 ejaculates were collected equally from 6 mature bucks at the weeklyinterval by using Artificial Vagina (AV) as per the standard procedure. All the ejaculates were diluted using six Skim milk-based extenders,viz. SME, SMGE, SMGH(1%)E, SMGH(2%)E, SMH(1%)E and SMH(2%)E. The sperm motility was evaluated by CASA (Computer AssistedSemen Analyzer). The data obtained was statistically analyzed. The results showed that sperm velocity parameters (VCL, VAP, and VSL)differed significantly (p
Keywords: Buck; CASA; Glutathione; Honey; Skim; milk; Sperm